Polyvinylidene fluoride piezoelectric composite film based on magnetized MXene grafted polyion liquid and preparation method thereof
Through magnetization MXene and grafting polyion liquid modification, combined with cycle and repeated folding melting mold technology, an efficient piezoelectric film was prepared, which solved the shortcomings of flexible piezoelectric materials in terms of piezoelectric properties, chemical stability and mechanical strength, and significantly Improves device performance and stability.
Patent Information
- Application Number
- CN202411277703.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
AI Technical Summary
Existing flexible piezoelectric materials have shortcomings in improving piezoelectric properties, chemical stability, mechanical strength and adaptability, especially in terms of long-term stability and mechanical strength, while the problems of stability and conductivity loss of pure MXene are affected. Its application.
The MXene was magnetized by chemical coprecipitation method, and the grafted polyion liquid was modified through RAFT polymerization and click chemical modification to enhance the polar crystal phase generation of PVDF. Combined with repeated folding of cycles and repeated folding of melting and compression molding, an efficient piezoelectric film was prepared to construct a layered structure. Improve piezoelectric performance.
It significantly improves the piezoelectric properties, chemical stability and mechanical strength of PVDF composite materials, extends the service life of the device, and enhances the recovery efficiency of mechanical energy and the interface coupling effect, solving the stability and conductivity loss problems of MXene.
Smart Images

Figure SMS_1 
Figure HDA0005040722430000011 
Figure HDA0005040722430000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer piezoelectric materials and discloses a polyvinylidene fluoride piezoelectric composite film based on magnetized MXene grafted polyionic liquid and a preparation method thereof. Background Art
[0002] The development and utilization of fossil energy faces various problems. Energy depletion and various environmental problems brought about by the use of fossil energy, such as chemical battery pollution, greenhouse effect, water pollution and air pollution, are constantly challenging the living environment of mankind. People are increasingly aware of the importance of developing renewable clean energy such as wind energy, solar energy, and tidal energy. Coupled with the rapid development of various portable electronic devices and the Internet of Things in modern society, there is an urgent need to develop high-performance, lightweight, and sustainable energy conversion and power supply equipment. However, despite the sufficient reserves of renewable energy, there are still some obstacles in the development and conversion process, such as high equipment cost, limited geographical location, and low conversion efficiency. At present, smart flexible wearable devices are widely used in medical monitoring, human-computer interaction, and artificial intelligence. These electronic devices and systems have made great progress in reducing power consumption, but energy supply and consumption are still the most critical limiting factors in the development of flexible electronics. Therefore, it is urgent to develop new flexible piezoelectric materials to provide energy for smart electronic products and avoid the use of harmful chemical batteries. Flexible piezoelectric materials have excellent mechanical properties, good environmental adaptability, and excellent energy harvesting performance. They can be integrated with electronic devices and wireless sensors to achieve self-powered, and are a good candidate.
[0003] Among various transduction pathways, piezoelectric conversion technology is often used as an effective way to convert vibration energy into electrical energy, with high electromechanical coupling coefficient and power density. The piezoelectric effect is that under the mechanical stimulation of external force, the material deforms, the central symmetry of the internal crystal structure is broken, polarized charges are generated, and an electric field is formed inside the material, which attracts or repels electrons on the upper and lower electrode surfaces, thereby generating piezoelectric potential in the piezoelectric material and realizing the conversion of mechanical energy to electrical energy. Therefore, materials with piezoelectric effect are piezoelectric materials that can convert mechanical energy into electrical energy. Among piezoelectric materials, polymers have good flexibility, light weight, adaptability and low acoustic impedance. Piezoelectric sensor devices prepared with polymers have ultra-high sensitivity, can respond quickly to changes in external parameters such as pressure and vibration, and have good durability and chemical stability. They can work stably for a long time under various environmental conditions. Therefore, they are widely used in many fields such as sensors. Polyvinylidene fluoride (PVDF), as the most flexible piezoelectric polymer material, has the advantages of smoothness, flexibility, lightness and fatigue resistance. The piezoelectric coefficient of its polarized film is as high as 6-7 pCN −1, which is 10 times that of other polymers. It has excellent piezoelectric, pyroelectric, ferroelectric and dielectric properties, and most importantly, it is adaptable to various forms of portable electronic devices. PVDF is a semi-crystalline polymer. Its piezoelectricity mainly depends on its crystal phase. There are five most common crystal phases: α, β, γ, δ and ε. The H atoms and F atoms on the α-crystal molecular chain are arranged alternately on both sides of the carbon chain (TG + TG - ), the chain dipole is opposite, so it has no apparent polarity and does not have piezoelectric, pyroelectric and ferroelectric properties. The piezoelectric properties of PVDF are attributed to the presence of polar crystal phases, including β and γ phases. The β crystal molecular chain is in an all-trans conformation (TTTT), and the unit cell contains a polar zigzag chain with high polarity and high spontaneous polarization. It exhibits the largest electric dipole moment among all crystal phases, so the β phase has the strongest polarity and has ferroelectricity and piezoelectricity; the F atoms and H atoms of the γ crystal molecular chain are arranged alternately in a reverse sequence (TTTG + TTTG - ), so that the γ phase can maintain piezoelectric properties and high crystallinity at higher temperatures, so that PVDF can be used in high-temperature environments within a certain temperature range. Therefore, increasing the content of polar β phase in PVDF is an effective way to improve the piezoelectric properties of PVDF-based piezoelectric sensors, actuators and energy harvesters.
[0004] Two-dimensional nanomaterials MXene (Ti3C2T x) The rich surface groups of PVDF help to form hydrogen bonds between the CF2 / CH2 groups of PVDF and the surface functional groups of MXene. Therefore, MXene has been proven to be an effective nucleating agent for enhancing the β-phase crystallization of PVDF. In addition, due to the microcapacitor effect, MXene has a two-dimensional geometry and conductive properties, which greatly enhances the piezoelectric output and provides a good candidate material for practical applications. However, pure MXene is prone to oxidative hydrolysis or aggregation when exposed to air, resulting in automatic stacking, and its stability is not high, which affects the electrical and mechanical properties of MXene and hinders its subsequent development. Through research, it was found that the introduction of ionic liquid (IL) polymerization grafting between the MXene layer structure can increase the interlayer spacing, prevent the stacking problem of MXene, and cooperate with MXene to promote the polar phase crystallization of PVDF and increase the piezoelectric properties of the composite material. In recent years, MXene has attracted great attention for its potential application in various magnetic technologies. Due to its superior electrical conductivity, MXene leads to stronger electrical conductivity loss and polarization loss. Its rich functional groups and defects on the surface are easily affected by polarization relaxation and scattering effects, forming a conductive network. Therefore, adding other magnetic or dielectric materials as modifiers is considered to be an effective strategy to improve the performance of MXene. Among various magnetic materials, Fe3O4 has a higher saturation magnetization and Curie temperature, and has a lower cost. After being magnetized by Fe3O4, MXene has mutual forces, which can build a micro-capacitor network in the PVDF matrix, significantly amplify the interface polarization effect, and fully release the magnetic response effect.
[0005] PVDF-based flexible devices have attracted much attention as self-powered power sources due to their excellent flexibility, high strength, easy processing and low cost. They are currently widely used in the fields of sensors and actuators. Over the years, people have been exploring ways to improve the generation of polar β phase in PVDF through filler selection, structural design and processing technology to optimize PVDF devices. It is reported that adding inorganic fillers with high dielectric constants or conductive fillers with high conductivity to the PVDF matrix can increase the polar β phase content of PVDF composites, thereby promoting the arrangement of microscopic dipoles in the composite material and affecting the piezoelectric properties and responsiveness of the composite material. The stable nanocharges of nanomaterials can improve the dielectric properties of PVDF and make it have good chemical flexibility, chemical stability and chemical hardness. The improvement of PVDF performance by nanomaterials is mainly manifested in four aspects: (1) improving the piezoelectric effect of PVDF; (2) promoting the nucleation and crystallization of PVDF polar phase; (3) constructing a conductive network; (4) acting as a stress concentration point to cause local deformation of PVDF and improve piezoelectric performance. These fillers can not only act as nucleating agents to promote the crystallization of PVDF, but also provide additional piezoelectric effect.
[0006] In addition to adding fillers to PVDF, its preparation process is also one of the key factors affecting the piezoelectric properties of PVDF. In most cases, a stable non-polar α phase is generated inside the prepared PVDF film, which lacks piezoelectric properties. In order to ensure that the dipole moment of the disordered molecules in PVDF can be oriented in a specific direction to form an excellent piezoelectric β phase, the content of the polar phase in PVDF can be increased by stretching, applying a strong electric field polarization and thermal annealing, thereby inducing dipole orientation. Common preparation methods include spin coating, electrospinning and hot pressing. The piezoelectric properties of the material in the hot pressing method are not only related to the characteristics of the PVDF matrix, but the factors of temperature and pressure during the molding process are also very important.
[0007] In addition, structural design of the PVDF sensing layer can further accelerate the electromechanical conversion capability and improve the output performance of the device. This is because the microstructured PVDF, in addition to having a higher crystallinity than the flat surface PVDF, will produce greater mechanical flexibility and displacement under specific stress, resulting in higher output yield. Although the development and design of various PVDF functional devices have made great progress, there are still many obvious problems to be solved: (1) Improve piezoelectric parameters and increase output voltage and power density; (2) Improve structural design to ensure the long-term stability and mechanical strength of the sensor device, making the research more targeted. (3) Improve the chemical stability, mechanical strength and chemical flexibility of piezoelectric composites. (4) Improve the adaptability and packaging of piezoelectric composites to any form of electronic devices. (5) Optimize the electromechanical conversion efficiency and the recovery efficiency of mechanical energy in various situations. (6) Limit and slow down the depolarization and aging process. (7) Improve the compatibility of composite components. Summary of the invention
[0008] In view of the above problems, the purpose of the present invention is to provide a polyvinylidene fluoride piezoelectric composite film based on magnetized MXene grafted polyionic liquid and a preparation method thereof. The present invention magnetizes MXene by chemical coprecipitation method, increases the interaction between MXene layers and expands the interlayer spacing; uses covalent modification method to modify the grafted polyionic liquid on the surface of magnetized MXene, which can effectively improve the generation of polar crystal phase of PVDF, and combines loading cycle repeated folding melt compression molding to prepare efficient piezoelectric film.
[0009] The present invention is achieved through the following technical solutions: A method for preparing a polyvinylidene fluoride piezoelectric composite film based on magnetized MXene grafted polyionic liquid comprises the following steps: (1) Soluble salts of divalent iron and trivalent iron are prepared into a precursor solution, and the precursor solution is added to an aqueous solution of thiolated MXene (MXene-SH) for sufficient reaction; NaOH solution is added as a precipitant, and after reacting at 90 °C for 5 h, nanoparticles of ferrosoferric oxide are formed and complexed on the surface of MXene to obtain magnetized MXene-SH (mMXene-SH).
[0010] Among them, the preparation method of MXene-SH is as follows: pre-prepare hydrofluoric acid with lithium fluoride and concentrated HCl, etch the aluminum layer in titanium aluminum carbide to obtain the two-dimensional nanocarbon material MXene; then use the intercalation agent dimethyl sulfoxide to intercalate the MXene to open the layer structure; then use thioacetic acid to react with the hydroxyl groups on the surface of MXene to graft thiol groups to obtain thiolated MXene.
[0011] In this step, MXene is first modified with thiol and then magnetized. MXene-SH can enhance the Ti-Fe hybridization synergistic strategy on the surface of nanosheets, resulting in the spontaneous formation and rapid agglomeration of Fe3O4 nanoparticles containing magnetic domains, and the mutual influence increases the magnetic domain content.
[0012] (2) generating an ionic liquid intermediate by reacting a brominated alkane with vinyl imidazole, and then replacing the ions with potassium hexafluorophosphate to synthesize an ionic liquid monomer; grafting the ionic liquid with an acetylenic monomer by RAFT polymerization to obtain a block copolymer of a polyionic liquid; (3) Through thiol-alkyne click chemistry, the magnetized thiol MXene surface obtained in step (1) is polymerized and grafted with the ionic liquid in step (2) to obtain a magnetized MXene grafted polyionic liquid, referred to as mMXene@PIL; (4) adding the MXene@PIL obtained in step (3) to a PVDF matrix and dispersing the MXene@PIL uniformly, removing the solvent to form a gel, melt-molding the gel to prepare a PVDF piezoelectric composite film, repeatedly folding and then molding the MXene@PIL to construct a layered structure in the PVDF composite film, and the thickness of the composite film remains substantially unchanged; (5) Polarizing and packaging the PVDF film obtained in step (4) to obtain a polyvinylidene fluoride piezoelectric composite film.
[0013] Furthermore, the raw material titanium aluminum carbide required for preparing MXene in step (1) has a purity of ≥98% and a particle size of 200-400 mesh.
[0014] Furthermore, the brominated alkane in step (2) may have any alkyl chain length, and preferably, the brominated alkane is any one of 1-bromohexane, 1-bromobutane or 1-bromooctane.
[0015] Furthermore, the vinyl imidazole in step (2) is any one of 1-vinylimidazole and 2-vinylimidazole.
[0016] Furthermore, the ionic liquid monomer described in step (2) is a hexafluorophosphate type ionic liquid.
[0017] Furthermore, the RAFT agent used in step (2) is cyanoisopropyl dithiobenzoate (CPDB), which is synthesized by reaction of bromobenzene, magnesium powder, carbon disulfide, sodium hydroxide, and K3[Fe(CN)6] solution, with iodine and AIBN as the initiator system.
[0018] Furthermore, the alkynyl monomer in step (2) is alkynyl propionate (PgMA), and PgMA is block copolymerized with the ionic liquid to provide alkynyl groups for the ionic liquid.
[0019] Furthermore, the alkynyl monomer PgMA is synthesized from propargyl alcohol, triethylamine and methacryloyl chloride, the reaction conditions are an ice bath, the polymerization time is 24 h, and the polymerization reaction is carried out in an organic solvent of dichloromethane.
[0020] Furthermore, in step (2), PgMA is block copolymerized with the ionic liquid, the initiators are DMA (N,N-dimethylaniline) and benzoyl peroxide (BPO), the amount used is 0.5% - 1% of the mass of the ionic liquid monomer, the polymerization temperature is 30-45°C, the polymerization time is 16-24 h, and the polymerization reaction is carried out in the organic solvent acetonitrile.
[0021] Furthermore, the click chemistry system in step (3) is a click of a thiol group and an alkynyl group, wherein the thiol group is provided by thiolated MXene and the alkynyl group is provided by alkynyl propionate (PgMA), and the ionic liquid is polymerized and clicked onto the MXene surface.
[0022] Furthermore, the mMXene@PIL added in step (4) is 1-10% of the mass of PVDF.
[0023] Furthermore, in step (4), the temperature of the melt molding is 170° C. and the pressure is 10 MPa.
[0024] Furthermore, the step (4) is cyclically folded repeatedly into a "pressing and folding" cycle. In the "pressing and folding" cycle, the composite film undergoes multiple stretching and melting cooling recrystallization to form a layered structure.
[0025] Furthermore, the encapsulation process in step (5) is to first apply conductive silver paste on the PVDF film as an electrode, cure it in an oven at 60-80°C for 1-6 h, then polarize it, pour polydimethylsiloxane (PDMS) liquid into the mold, then put the PVDF film into it, and cure it at 60-80°C for 1-6 h for encapsulation. The preparation method of PDMS liquid is: PDMS and curing agent are stirred evenly at a mass ratio of 10:1, and bubbles are removed by vacuum.
[0026] Furthermore, the polarization in step (5) is as follows: the PVDF composite film is cut into a rectangle of 2 cm × 3 cm, and then a conductive silver paste is applied on the surface thereof. The area of the conductive silver paste should be slightly smaller than the area of the composite film to prevent the conductive silver paste on the upper and lower surfaces of the film from contacting each other and causing a short circuit. Then, the composite film is placed in a silicone oil bath and placed at 50 MV⋅m -1 The composite film was polarized for 3 h under a polarization electric field of 1.50 nm. Finally, the composite film was discharged for 24 h.
[0027] The present invention adopts the method of RAFT polymerization combined with click chemistry to modify the surface of MXene by grafting polyionic liquid. Due to the strong π-π interaction and hydrogen bonding between PVDF and MXene, the formation of polar crystal phase of PVDF can be effectively improved to prepare efficient piezoelectric film, thereby encapsulating and preparing devices. Compared with the prior art, it has the following beneficial effects: After thiol modification of MXene, the present invention adopts a chemical coprecipitation method to prepare Fe3O4 magnetized MXene-SH. The thiol modification of MXene can enhance the Ti-Fe hybridization synergistic strategy on the surface of nanosheets, resulting in spontaneous formation and rapid aggregation of Fe3O4 nanoparticles containing magnetic domains, and the mutual influence increases the magnetic domain content.
[0028] The present invention uses RAFT polymerization and click chemistry to select ionic liquids (IL) with different alkyl chain lengths (1-vinyl-3-butyl imidazole hexafluorophosphate, 1-vinyl-3-hexyl imidazole hexafluorophosphate, 1-vinyl-3-octylimidazole hexafluorophosphate) and PgMA to synthesize block copolymers, and through the double bond polymerization of the vinyl group of IL, PgMA provides the alkynyl group required for click chemistry, and PIL is introduced into the MXene interlayer to synthesize MXene@PIL. Click chemistry can further increase the grafting rate of PIL on the MXene surface. At the same time, the ion-dipole interaction between the imidazole ring on the PIL and the -CF2 on the PVDF segment causes PVDF to transform from the α phase to the β phase.
[0029] When pressing the PVDF composite film, a "pressing & folding" cycle is used to create a layered structure in the PVDF film to prepare the PVDF / mMXene@C6PIL composite piezoelectric film. Under the "pressing and folding" cycle, the composite film undergoes multiple stretching and melting cooling recrystallization, which in turn promotes the transformation of part of the α phase into the β phase, and the β phase content increases; the multiple interfaces generated by the layered structure inside the PVDF composite material have super strong interface coupling, ionic interaction and Coulomb blocking effect, which increases the interface effect and β phase stretching crystallization, and the piezoelectric performance of the PVDF composite film is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 XRD spectra of unmagnetized MXene@PIL grafted with different ionic liquids in Examples 1-3.
[0031] Figure 2 Infrared spectra of Fe3O4 nanoparticles, mMXene@C6PIL and mMXene-SH in Example 4.
[0032] Figure 3 Magnetic hysteresis loops of Fe3O4 nanoparticles, mMXene@C6PIL and mMXene-SH in Example 4.
[0033] Figure 4 Infrared spectra of the PVDF / MXene@PIL composite films prepared in Examples 1-3 and the PVDF composite films under each “pressing and folding” cycle in Examples 4-6 and the relative content of β phase in the PVDF composite films.
[0034] Figure 5 SEM images of the surface (left) and cross-section (right) of the PVDF / MXene@PIL composite film in Examples 1-3.
[0035] Figure 6 SEM images of the surface (left), cross-section (middle) and cross-section crystal structure (right) of the PVDF composite film under each "pressing and folding" cycle in Examples 4-6.
[0036] Figure 7 The dielectric constant (a) and dielectric loss (b) of the PVDF composite film under each "pressing and folding" cycle in Example 1 and Examples 4-6.
[0037] Figure 8 (a) piezoelectric charge coefficient d of the PVDF composite film under each "pressing and folding" cycle in Example 1 and Examples 4-6 33 (b) Piezoelectric voltage coefficient g 33 and (c) piezoelectric performance (FOM) diagram.
[0038] Fig. 9 (a) hysteresis loop (PE loop), (b) energy storage efficiency η, and (c) breakdown strength of the PVDF composite film under each "pressing and folding" cycle in Example 1 and Examples 4-6. DETAILED DESCRIPTION
[0039] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0040] The present invention is further described in detail below in conjunction with embodiments: Performance testing method:
[0041] The prepared samples were subjected to infrared testing and analysis according to the method disclosed in CN114031797A, and the content of β-crystal in PVDF was calculated; the free capacitance and dielectric loss of the samples were tested, and the dielectric constant was calculated.
[0042] XRD diffraction test: Use X-ray diffraction in the crystal to obtain the crystal structure, unit cell parameters, etc. It is helpful to observe the crystal structure and analyze the crystal phase in PVDF. Set the test speed to 6° / min, the 2θ angle scanning range to 0-60°, and select Cu-K α Rays are used for measurement.
[0043] SEM test: Cut the PVDF film into 0.5 cm × 0.5 cm, then fix it on a cylindrical mold with conductive glue, spray gold on the surface of the film, and observe the surface morphology. Film cross-sectional morphology test: First, place a film of 1 cm × 2 cm in liquid nitrogen to make it brittle, then fix the film again, spray gold, and test.
[0044] Piezoelectric performance test: The sample was cut into 1 cm × 1 cm, and conductive silver paste was coated on the upper and lower surfaces of the film as the upper and lower electrodes of the composite film. It was then wrapped with aluminum foil and thermally polarized in silicone oil. It was placed in a 10 kV high voltage polarization field with an electric field strength of 4000 V / m and a temperature of 90 °C for 1 h. After the polarized sample cooled to room temperature, the wrapped film was placed in a d 33 Test on the instrument. Example 1
[0045] A PVDF piezoelectric film based on unmagnetized MXene grafted polyionic liquid C6PIL is prepared by the following method: Step 1: Add lithium fluoride (2 g) and concentrated HCl (98%, 35 mL) to a polytetrafluoroethylene cup to pre-prepare hydrofluoric acid, then add 1 g of titanium aluminum carbide (Ti3AlC2) powder for etching, react in an oil bath at 40-50 °C for 36 h, and then centrifuge and wash with deionized water until the upper clear liquid is neutral. Disperse MXene (1 g) in DMSO (60 mL) and ultrasonicate for 1.5 h to intercalate MXene. After intercalation, continue to centrifuge and wash with deionized water and anhydrous ethanol to obtain MXene powder.
[0046] Step 2: Disperse the MXene in step 1 evenly in 200 ml of water, take 20 ml and react with 1 ml of thioglycolic acid for esterification, and react for 24 h in a nitrogen environment at an oil bath temperature of 75 °C. After the reaction is completed, wash with acetone and deionized water and freeze-dry to obtain MXene-SH.
[0047] Step 3: Dissolve 10 mL of 1-vinylimidazole and 10 mL of 1-bromohexane in 60 mL of acetonitrile, and stir the mixture under nitrogen atmosphere at 75 °C for 24 h to obtain a C6 ionic liquid intermediate. Dissolve the intermediate in acetonitrile and ethyl acetate, separate the liquids, add it to a potassium hexafluorophosphate solution, and react it in an oil bath at 90 °C for 24 h. After the reaction, remove the deionized water by rotary evaporation to obtain the desired ionic liquid monomer C6IL.
[0048] Step 4: Dissolve the ionic liquid monomer and acetylenic monomer PgMA in acetonitrile solvent, weigh 0.05 g of RAFT agent CPDB as the chain transfer agent of the reaction system, 0.022 g of BPO as the initiator, and 30 µl of DMA (N,N-dimethylaniline) as the initiator to initiate BPO, so that the BPO initiation system can react. React in a water bath at 30 ° C in a nitrogen environment for 24 h. After the reaction, use petroleum ether to dissolve the small molecule product of the polymerization. The oily substance in the lower layer that cannot be dissolved is the block copolymer C6PIL-r- PgMA of the polyionic liquid.
[0049] Step 5: Graft the block copolymer from step 4 onto the surface of MXene-SH from step 2. Dissolve 0.1 g MXene-SH, 0.2 g C6PIL-r-PgMA block and 0.1 g photoinitiator 1173 (2-hydroxy-2-methylpropiophenone) in 25 ml acetonitrile and heat at 30 °C for 6-8 h under nitrogen atmosphere. 乙醇 :V 水 =1:1 mixed solution was centrifuged and washed, and finally vacuum freeze-dried to obtain MXene@C6PIL modified particles.
[0050] Step 6: Dissolve 0.2 g of MXene@C6PIL in 9 ml DMF (NN dimethylformamide) and disperse evenly, then dissolve 2 g of PVDF powder in 9 ml DMF and disperse, mix the two solutions together and place them on a stirring table, and further mix them evenly at 60 °C for 3 h. Pour the mixed solution into a watch glass, place it in a vacuum oven to evaporate the solvent, and form a gel film after drying.
[0051] Step 7: The gel film in step 6 was melt-molded using a flat vulcanizer at a pressure of 10 MPa and a temperature of 180 °C to prepare a PVDF / MXene@C6PIL composite piezoelectric film with a thickness of 2 µm and a 10 wt % MXene@PIL.
[0052] Step 8: Polarize the PVDF composite piezoelectric film obtained in step 7 and encapsulate it to prepare a PVDF flexible piezoelectric nano-power generation sensor. After polarizing the PVDF film, first adhere copper sheets to the upper and lower surfaces of the PVDF film with conductive silver glue, and cure it in an oven at 60-80°C for 1-6 h. Stir polydimethylsiloxane (PDMS) and curing agent at a mass ratio of 10:1 for 5 min, remove bubbles in vacuum, pour into a mold, place the PVDF composite piezoelectric film in PDMS and encapsulate it, dry it at 60-80°C (generally dry it for 1-4 h), and cure it at room temperature (generally cure it for about 24 h). Example 2
[0053] A method for preparing a PVDF piezoelectric film based on unmagnetized MXene grafted polyionic liquid C4PIL is prepared by the following method: The preparation of MXene@C4PIL modified particles is different from that in Example 1. Step 3: 10 mL of 1-vinylimidazole and 10 mL of 1-bromohexane are dissolved in 60 mL of acetonitrile, and stirred for reaction at 75 °C for 24 h under a nitrogen atmosphere to obtain a C4 ionic liquid intermediate. The intermediate is dissolved and separated in acetonitrile and ethyl acetate, respectively, added to a potassium hexafluorophosphate solution, and reacted in an oil bath at 90 °C for 24 h. After the reaction, the deionized water is removed by rotary evaporation to obtain the desired ionic liquid monomer C4IL. The remaining steps refer to Example 1 to prepare MXene@C4PIL modified particles.
[0054] The PVDF piezoelectric film was prepared by referring to steps 5-8 of Example 1 to prepare PVDF / MXene@C4PIL with 10 wt % MXene@PIL. Example 3
[0055] A method for preparing a PVDF piezoelectric film based on unmagnetized MXene grafted polyionic liquid C8PIL is prepared by the following method: The preparation of MXene@C8PIL modified particles is different from that in Example 1. Step 3: 10 mL of 1-vinylimidazole and 10 mL of 1-bromooctane are dissolved in 60 mL of acetonitrile, and stirred for reaction at 75 °C for 24 h under a nitrogen atmosphere to obtain a C8 ionic liquid intermediate. The intermediate is dissolved and separated in acetonitrile and ethyl acetate, respectively, added to a potassium hexafluorophosphate solution, and reacted in an oil bath at 90 °C for 24 h. After the reaction, the deionized water is removed by rotary evaporation to obtain the desired ionic liquid monomer C8IL. The remaining steps refer to Example 1 to prepare MXene@C8PIL modified particles.
[0056] The PVDF piezoelectric film was prepared by referring to steps 5-8 of Example 1 to prepare PVDF / MXene@C8PIL with 10 wt % MXene@PIL. Example 4
[0057] A scheme for preparing a magnetized MXene@C6PIL modified particle composite PVDF piezoelectric film is prepared by the following method: Step 1: Preparation of MXene-SH is the same as in Example 1.
[0058] Step 2: Dissolve 1.5 g of ferrous sulfate heptahydrate and 1.5 g of ferric chloride hexahydrate in 10 mL of deionized water to prepare a precursor. Take 1 mL of the precursor and add it to 40 mL of an aqueous solution containing MXene (5 mg / mL) and react at 80 °C for 2 h to cause an ion exchange reaction at the Ti-OH end to form a layered Ti-O-Fe + Take 2.4 g of NaOH and dissolve it in 10 mL of deionized water. Take 1 mL of NaOH solution and add it to the precursor solution. NaOH converts the metal salt into hydroxide, and then into ferrite. After reacting at 90 °C for 5 h, a magnetic material is formed to obtain magnetized MXene-SH (mMXene-SH).
[0059] Step 3: The preparation method of the polyionic liquid block copolymer C6PIL-r-PgMA is the same as that in Example 1.
[0060] Step 4: Graft the block copolymer of step 3 onto the surface of mMXene-SH of step 2. Dissolve 0.1 g mMXene-SH, 0.2 g C6PIL-r-PgMA block and 0.1 g photoinitiator 1173 (2-hydroxy-2-methylpropiophenone) in 25 ml acetonitrile and heat at 30 °C under nitrogen atmosphere for 6-8 h.乙醇 :V 水 =1:1 mixed solution was centrifuged and washed, and finally vacuum freeze-dried to obtain mMXene@C6PIL modified particles.
[0061] Step 5: Dissolve 10 wt% of mMXene@C6PIL in 9 ml of DMF (NN dimethylformamide) and disperse evenly, then dissolve 2 g of PVDF powder in 9 ml of DMF and disperse, mix the two solutions together and place them on a stirring table, and further mix them evenly at 60 °C for 3 h. Pour the mixed solution into a watch glass, place it in a vacuum oven to evaporate the solvent, and form a gel film after drying.
[0062] Step 6: The gel film in step 5 was melt-molded using a flat vulcanizer at a pressure of 10 MPa and a temperature of 180 °C to prepare a PVDF composite piezoelectric film. One "pressing & folding" cycle was performed to obtain a PVDF / mMXene@C6PIL composite piezoelectric film with an average film thickness of 2 µm.
[0063] Step 7: Polarize the PVDF composite piezoelectric film obtained in step 6 and then encapsulate it. After polarizing the PVDF film, adhere copper sheets to the upper and lower surfaces of the film with conductive silver glue, and cure it in an oven at 60-80°C for 1-6 hours. Stir polydimethylsiloxane (PDMS) and curing agent at a mass ratio of 10:1 for 5 minutes, remove bubbles in vacuum, pour into a mold, encapsulate the PVDF composite piezoelectric film in PDMS, dry it at 60-80°C (generally dry it for 1-4 hours), and cure it at room temperature (generally cure it for about 24 hours). Example 5
[0064] The difference between this embodiment and embodiment 4 is that in step 6, three "pressing & folding" cycles are performed to prepare a PVDF / mMXene@C6PIL-3 composite piezoelectric film with an average film thickness of 2 µm. Example 6
[0065] The difference between this embodiment and embodiment 4 is that in step 6, 6 “pressing & folding” cycles are performed to prepare a PVDF / mMXene@C6PIL-6 composite piezoelectric film with an average film thickness of 2 µm.
[0066] Characterization and performance test results:
[0067] Figure 1The XRD spectra of ILs with three different alkyl chain lengths grafted onto MXene. The diffraction peak at 2θ = 9.4° gradually increases, corresponding to the (002) crystal plane. The diffraction peaks of MXene@C4PIL at (101) and (105) crystal planes become strong peaks at 38.9°, corresponding to the (104) crystal plane. As the alkyl chain length of PIL increases, the intensity of the diffraction peak gradually increases, proving that grafting of PIL between MXene sheets will expand its interlayer spacing. The longer the alkyl chain length, the larger the interlayer spacing.
[0068] Figure 2 Infrared spectra of Fe3O4 nanoparticles and mMXene. 615 cm -1 The absorption peak at 1617 cm corresponds to the Fe-O characteristic stretching absorption peak of Fe3O4. -1 The peak at 3414 cm represents the stretching vibration peak of FeO-. -1 The broad peak at 3 O 4 The stretching vibration peak of the surface hydroxyl -OH is at 700 cm -1 There is a characteristic absorption peak without ferrous oxygen bond near 561 cm -1 The broad absorption peak appearing at is the composite vibration of the strong Ti-O peak of MXene and the Fe-O characteristic absorption peak of Fe3O4, proving the existence of intercalation of Fe3O4 nanoparticles, indicating that MXene-SH and MXene@C6PIL are successfully magnetized.
[0069] Figure 3 The hysteresis loops of Fe3O4 and mMXene. The hysteresis curves of Fe3O4, mMXene-SH and mMXene@C6PIL all pass through (0,0), indicating that the residual magnetic field strength (B r ) and coercive force (HD) are both 0, which shows good superparamagnetism. The saturation magnetic induction intensity of Fe3O4 is 43 emu / g, and the saturation magnetic induction intensity of mMXene-SH and mMXene@C6PIL are 37emu / g and 23 emu / g, respectively, indicating that after PIL is grafted on the surface of mMXene-SH, the magnetic induction intensity of mMXene@PIL decreases. Compared with Fe3O4, the magnetic induction intensity of mMXene-SH in low magnetic field is higher than that of Fe3O4, which may be due to the fact that MXene thiolation enhances the Ti-Fe hybridization synergistic strategy on the surface of nanosheets, resulting in the spontaneous formation and rapid agglomeration of Fe3O4 nanoparticles containing magnetic domains, and the mutual influence increases the content of magnetic domains. However, due to the surface grafting of PIL on mMXene@C6PIL, the clustered Fe3O4 nanoparticles are dispersed, resulting in a decrease in magnetic induction intensity.
[0070] Figure 4 (a) is the infrared spectrum of PVDF composite film under each “pressing and folding” cycle. -1 and 1070 cm -1 The skeleton bending and stretching vibration peak of -CF2 appears at 1161 cm -1 、874cm -1 and 838 cm -1 The characteristic peak of β-PVDF appears at 593 cm -1 The peak at 614 cm is the characteristic peak of non-polar α-PVDF. Compared with the PVDF / MXene@C6PIL composite film, the PVDF / mMXene@C6PIL composite film after magnetization of MXene has a -1 The characteristic peak of non-polar α-PVDF at 475 cm-1 is not obvious, indicating that the presence of magnetic Fe3O4 particles can strengthen the interaction between MXene@PIL and PVDF segments, making PVDF form an ordered all-trans conformation. -1 The Fe-O stretching vibration peak appears at the MXene, indicating that the MXene is successfully magnetized. Under the "pressing and folding" cycle, the composite film undergoes multiple stretching and melting cooling recrystallization, which promotes the transformation of part of the α phase into the β phase, and the β phase content increases. The peak positions of the PVDF / mMXene@C6PIL composite film under each cycle are basically the same, only the peak area intensity changes, and the β phase content is 99.7%. Figure 4 (b) This indicates that mMXene@C6PIL interacts with PVDF segments, causing the PVDF segments to arrange in an orderly manner and inducing the formation of polar phases. At the same time, the number of stretching cycles affects the crystal structure of PVDF. As the number of cycles increases, the β-phase crystallization gradually increases. Figure 4 (c) is the infrared spectrum of the PVDF composite film with 10 wt% MXene@PIL added. The peak positions did not change significantly. After click chemistry modification, PILs with different alkyl chain lengths were grafted onto the MXene surface. The alkyl chain length affects the conductivity of the IL and the interlayer spacing of the MXene. The synergistic effect of the two makes MXene@PIL have different effects on the crystallization of the PVDF polar phase. At the same time, the ion-dipole interaction between the imidazolium cation in the PIL and the -CF2 in the PVDF segment further promotes the nucleation of the β phase. The relative content of the β phase of PVDF / MXene@C6PIL reaches 99.3%, as shown in Figure 2. Figure 4 (d).
[0071] After PIL was grafted onto the surface of MXene, the length of the alkyl chain increased. Figure 5From the cross-sectional view of the middle film, it can be seen that large-sized grains are gradually replaced by small-sized grains, which means that the grafting of PIL between MXene nanosheets strengthens the transformation of α crystals to β crystals in PVDF. Since MXene@PIL is well dispersed in the PVDF matrix and no phase separation occurs, it means that MXene@PIL is inserted into the PVDF chain segment in an orderly manner, has good thermodynamic compatibility, and the surface of the PVDF membrane tends to be smooth. MXene@PIL alleviates the disadvantage of MXene's easy hydrolysis, and further promotes the crystallization of PVDF polar phases, enhancing the performance of PVDF composite films. PVDF / MXene@C8PIL begins to show large-sized grains again, and there is a phase separation phenomenon, indicating that the excessively long PIL alkyl chain restricts the movement of the PVDF matrix chain segment and hinders the crystallization of the polar phase.
[0072] PVDF can undergo high pressure, stretching and other processes to make its chain segments show maximum polarization, that is, form a polar β phase. Figure 6 The SEM images of the surface (left), the whole cross section (middle) and the cross section crystal form (right) of the PVDF composite film are shown in the figure. After three cycles of "pressing and folding", the surface of the composite film is more compact, with obvious traces of loading stripes, a layered structure and a smaller grain size. This is because the composite film undergoes multiple melt stretching and cooling recrystallization, giving the PVDF molecular segments enough energy to arrange the segments regularly and transform them into an ordered all-trans conformation. In addition, the interlayer spacing of MXene is expanded during the melt stretching process, which promotes the interfacial compatibility between MXene and its interlayer grafted PIL and the PVDF matrix, and gives full play to the role of MXene nucleating agent and PIL nanostructurant, prompting PVDF to continuously form β-crystalline nuclei, increase the number of crystal nuclei, and have limited space for unit cell growth, so the grain size becomes smaller. In addition, the attachment of magnetic Fe3O4 nanoparticles to MXene@C6PIL can increase the interaction between its layers, prevent the stacking and oxidation of MXene@C6PIL, increase dispersibility, and avoid phase separation. After 6 cycles of “pressing and folding”, the loading marks on the surface of the composite film are more obvious, the layered structure of the PVDF composite film can be seen more clearly, and the number of crystal nuclei is greatly increased, resulting in small grain size and dense β crystals.
[0073] Magnetic Fe3O4 particles attach to the Ti-O end of MXene to form a strong complex, which can generate interaction forces between the layers to prevent the oxidation of MXene from self-stacking and improve the magnetic separation force of MXene. Reducing MXene self-stacking exposes more active surfaces, with higher charge storage capacity, providing more movement space for the PIL chains between MXene sheets. At the same time, the contact between MXene and PVDF matrix will produce an interface effect, increase the interface polarization, and realize the transmission of electrons between MXene layers, thereby improving the dielectric constant of the composite material. Figure 7 (a), the dielectric constant of PVDF / mMXene@C6PIL after magnetization with Fe3O4 is greatly improved. In addition, Fe3O4 nanoparticles have a highly active surface and a high surface area, and their catalytic activity can be enhanced by loading non-metallic or carbonaceous materials. Since MXene nanosheets are conductive, the electrons of Fe3O4 are easily transferred to the MXene surface, thereby achieving better charge separation, which is manifested as an improvement in the dielectric properties of PVDF composites. By applying a "pressing and folding" cycle to PVDF, a layered structure is prepared to further enhance the interface effect. MXene is dispersed in PVDF, and under the action of the electric field, the dipoles tend to polarize by accumulating the charges existing between the PVDF matrix and the MXene interface, resulting in MWS polarization. With the increase in the number of cycles, the dielectric constant of the PVDF composite material gradually increases, and the dielectric constant of PVDF / mMXene@C6PIL-6 reaches 1645. Figure 7 (b) is the dielectric loss of PVDF composite film under the "pressing and folding" cycle. The dielectric loss of PVDF / MXene@C6PIL is the highest under low electric field. After magnetization, the dielectric loss of PVDF / mMXene@C6PIL is reduced. This is because the magnetic particles Fe3O4 are complexed with MXene and distributed in the PVDF matrix together with MXene. Its ultra-high conductivity optimizes the conductivity of MXene. The difference in dielectric constants between mMXene@C6PIL and PVDF produces electronic defects and holes at the interface of the two components, which inhibits the migration of charge carriers and reduces the dielectric loss of the composite film. After the "pressing and folding" cycle, it was found that the dielectric loss of PVDF / mMXene@C6PIL-3 after 3 cycles was the lowest. With the increase in the number of cycles, the dielectric loss of PVDF / mMXene@C6PIL-6 increased again. It may be due to the fact that multiple cycles increase the internal interface layer of PVDF, the electron transmission path becomes longer, and the multiple conductive pathways increase the leakage current of the material, resulting in increased dielectric loss. However, the interface polarization and barrier effect can still enable the PVDF composite material to maintain a lower dielectric loss and a higher dielectric constant overall.
[0074] Figure 8(a) is the piezoelectric coefficient of the PVDF composite film that has undergone a "pressing and folding" cycle. After magnetization, the piezoelectric coefficient of PVDF / mMXene@C6PIL increases because the magnetic particles Fe3O4 increase the interlayer spacing of MXene, thereby enhancing the interfacial compatibility between MXene and PVDF. After applying the "pressing and folding" cycle, the multiple interfaces generated by the layered structure inside the PVDF composite material have super strong interfacial coupling, ionic interaction, and Coulomb blockade effects, increasing the interfacial effect and β-phase stretching crystallization. With the increase in the number of cycles, the piezoelectric coefficient of the PVDF composite film gradually increases, and the piezoelectric coefficient of PVDF / mMXene@C6PIL-6 reaches 45 pCN -1 , which is 15 times higher than pure PVDF (~3). Figure 8 (b) is the piezoelectric charge coefficient g of each PVDF composite film 33 . Figure 8 (c) Predefined piezoelectric performance diagram (FOM) for each PVDF composite film. It can be seen from the figure that the piezoelectric charge coefficient and overall piezoelectric performance of PVDF / mMXene@C6PIL are greatly improved after magnetization and "pressing and folding" cycles.
[0075] Fig. 9 Investigating the ferroelectric properties of the film, (a) it can be seen that Fe3O4 can significantly improve the magnetism of MXene, change its behavior in response to electric fields, and contribute to the ferroelectric behavior of PVDF. At the same time, the "pressing and folding" cycle during the film making process will also affect the ferroelectric properties of the film. Table 1 shows the ferroelectric performance data of PVDF composite films. In the magnetized PVDF / mMXene@C6PIL composite film, the magnetic particles Fe3O4 attached to the surface of MXene greatly increase the interlayer spacing and surface area of MXene, and the interface polarization effect is enhanced. Under the action of the electric field, its energy density is also significantly improved, and the energy storage efficiency increases to 31%. After multiple cycles, the breakdown strength of the composite film is improved, and the energy density is significantly increased. After 6 cycles, the energy storage efficiency of the film is as high as 73.4%. (c) shows the maximum polarization rate P of the PVDF composite material. max The electric field strength under the condition of 100° is the breakdown strength of the PVDF composite film. Generally speaking, the breakdown strength of pure PVDF is between 30-80 MV / m. The PVDF / MXene@C6PIL composite film achieves a breakdown strength of 160 MV / m by interlayer grafting PIL on MXene. The breakdown strength of the magnetized PVDF / mMXene@C6PIL increases to 250 MV / m. Applying a "pressing and folding" cycle to the PVDF film-making process greatly enhances the breakdown strength of the PVDF composite film to an ultra-high 365 MV / m, without affecting its ultra-high dielectric properties.
[0076] Table 1 Ferroelectric properties of PVDF composite films under various “pressing and folding” cycles
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polyvinylidene fluoride piezoelectric composite film based on magnetized MXene grafted polyionic liquid, characterized in that: The following steps are involved: (1) MXene, a two-dimensional nanocarbon material, is thiolated to obtain MXene-SH; Fe3O4 is deposited on the surface of MXene-SH by chemical coprecipitation to obtain magnetized MXene-SH, denoted as mMXene-SH; (2) generating an ionic liquid intermediate by reacting a brominated alkane with vinyl imidazole, and then replacing the ions with potassium hexafluorophosphate to synthesize an ionic liquid monomer; grafting the ionic liquid with an alkynyl monomer through a RAFT polymerization reaction to obtain a block copolymer of a polyionic liquid; the brominated alkane is any one of 1-bromohexane, 1-bromobutane or 1-bromooctane; and the vinyl imidazole is 1-vinylimidazole or 2-vinylimidazole; (3) Through thiol-alkyne click chemistry, the mMXene-SH obtained in step (1) is polymerized and grafted with the ionic liquid in step (2) to obtain a magnetized MXene grafted polyionic liquid, denoted as mMXene@PIL; (4) adding the MXene@PIL obtained in step (3) to the PVDF matrix and dispersing it evenly, removing the solvent to form a gel, loading the gel and repeatedly folding the melt-molding to obtain a PVDF piezoelectric composite film; and then performing polarization packaging.
2. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: The preparation method of the MXene-SH is as follows: pre-prepare hydrofluoric acid with lithium fluoride and concentrated HCl, etch the aluminum layer in titanium aluminum carbide to obtain a two-dimensional nanocarbon material MXene; then use the intercalation agent dimethyl sulfoxide to intercalate the MXene to open the layer structure; then use thioglycolic acid to react with the hydroxyl groups on the surface of the MXene to graft the thiol group to obtain the thiolated MXene; the usage ratio of thioglycolic acid to MXene is 1mL:100mg.
3. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: Preparation method of magnetized MXene-SH: prepare a precursor solution with soluble salts of divalent iron and trivalent iron, add the precursor solution to an aqueous solution of MXene-SH for sufficient reaction; add NaOH solution as a precipitant to react to form nanoparticles Fe3O4 that are complexed on the surface of MXene to obtain magnetized MXene-SH; the ratio of the total molar amount of iron ions in the precursor solution to MXene-SH is 1 mol: 200 g.
4. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: In step (2), the RAFT agent is cyanoisopropyl dithiobenzoate; and the alkynyl monomer is alkynylpropyl methacrylate.
5. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: In step (2), PgMA is block copolymerized with the ionic liquid, the initiators are DMA (N,N-dimethylaniline) and benzoyl peroxide (BPO), the amount used is 0.5% - 1% of the mass of the ionic liquid monomer, the polymerization temperature is 30-45°C, the polymerization time is 16-24 h, and the polymerization reaction is carried out in the organic solvent acetonitrile.
6. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: The click chemistry system in step (3) is a click of a thiol group and an alkynyl group, wherein the thiol group is provided by thiolated MXene and the alkynyl group is provided by alkynyl propionate (PgMA), and the ionic liquid is polymerized and clicked onto the MXene surface.
7. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: The amount of mMXene@PIL added in step (4) is 1-10% of the mass of PVDF.
8. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: The temperature of the melt molding in step (4) is 170°C and the pressure is 10 MPa.
9. The method for preparing a polyvinylidene fluoride piezoelectric composite film based on a magnetized MXene grafted polyionic liquid according to claim 1, characterized in that: The polarization packaging process in step (5) is as follows: apply conductive silver paste as an electrode on the PVDF film and cure it in an oven at 60-80°C for 1-6 h; pour the PDMS liquid into the mold, then put the PVDF film into it, and heat it at room temperature at 50 MV⋅m -1 The film was polarized for 3 h under a polarizing electric field, discharged for 24 h, and finally cured at 60-80 °C for 1-6 h for packaging.
10. A polyvinylidene fluoride piezoelectric composite film prepared by the method of claims 1-9.
Citation Information
Cited By
Method for realizing MXene surface modification by using solid irradiation
CN119875203A
